Synthesis and properties of 1,6-difunctionalized cyclodeca-3,8-diynes - Rajesh, Sheela; Haberhauer, Gebhard; Feuerbacher, Sven; Rominger, Frank; Oeser, Thomas; Gleiter, Rolf (Synthesis, 2003)
The reaction of tert-butyl acetate (6) with 1,4-dibromobut-2-yne (1) in the presence of LDA yielded 1,6-di(tert-butyl)cyclodeca-3,8-diyne-1,6-dicarboxylate (8). The 1,6-di(tert-butyl) groups of 8 were transferred to bis(hydroxymethyl) (5), bis(bromomethyl) (13), bis(cyanomethyl) (14), dicarbaldehyde (15) and bis(methoxyvinyl) (16) groups. In case of 13 the two diastereomers [cis(a,e), trans(a,a)] were separated. From 13(a,e) and 14(a,a) we were able to obtain detailed structural parameters by means of X-ray crystallography. By means of temperature dependent NMR spectroscopy of 14(a,a) we estimated the activation energy for the chair-boat conversion to be 10.5 kcal/mol.